PROGRAM PEMBERDAYAAN EKONOMIMELALUI PELATIHAN PEMASARAN RENGGINANG IKAN TENGIRI PADA UD. YULIA & UD. FAHRUR DI DESA SEMIRING SELATAN KECAMATAN MANGARAN KABUPATEN SITUBONDO JAWA TIMUR - Nanik Hariyana; Lita Permata Sari; Hendra Syahputra (Relawan Jurnal Indonesia, 2017)
Economic empowerment program through marketing training tenggiri fish concerts at UD. Yulia & UD. Fahrur in the village south semiring mangaran district East Java situbondo regency. In addition to the need for programs that are able to improve the insight, skills, and experience to realize the program. Some problems faced such as 1. Low Promotion to the closest people, Low in Utilizing social media to expand marketing, Low in Cooperation with resellers, Low in Choosing a consignment system (selling titles), Low in Charge time off to open stalls in a strategic location. Through the program proposed by this devotee is the activity of community service by providing training through marketing training tengiri fish rengginang. Training on UD. Yulia and UD. Fahrurdesa Semiring Selatan RT 002 RW 003 Mangaran Subdistrict will be given provision of knowledge about MSME marketing training is good that is how the capital needs of a business, the expenditure should be spent to finance the production and how to determine the cost of products that can be profitable for his business. The last training is human resource management where the focus of training is to develop a disciplined attitude, courageous act, able to manage others and improve leadership goodness. Outcomes achieved are marketing training tengiri fish rengginang, Outcomes achieved from this devotion activities is the first scientific publication on the Journal of ISSN / Proceeding the National journal, the second publication on the media print / online / repocitory PT. thirdly Increased competitiveness (quality improvement, quantity, and value added goods, services, product diversification, or other resources), fourth Improvement of the application of science and technology in society (mechanization, IT, and management), fifth Improvement of community values ​​(cultural arts, social , politics, security, tranquility, education, health).